Ceftolozane/tazobactam for difficult‐to‐treat Gram‐negative infections: A real‐world tertiary hospital experience. (7th March 2022) - Ronda, Mar; Pérez‐Recio, Sandra; González Laguna, Mònica; Tubau Quintano, Maria de la Fe; Llop Talaveron, Josep; Soldevila‐Boixader, Laura; Carratalà, Jordi; Cuervo, Guillermo; Padullés, Ariadna
Abstract: Objective: To evaluate the real‐world clinical efficacy of ceftolozane/tazobactam (C/T) in difficult‐to‐treat infections caused by multi‐drug resistant Gram‐negative microorganisms, including carbapenem‐resistant Pseudomonas aeruginosa . Methods: Retrospective cohort study of adult patients treated with C/T for at least 48 hours for infections caused by multi‐drug resistant Gram‐negative bacteria in a tertiary hospital from May 2016 until August 2019. The primary outcome analysed was clinical failure, defined as a composite of symptomatology persistence after 7 days of C/T treatment, infection recurrence, and/or all‐cause mortality within 30 days of follow‐up. Results and discussion: 96 episodes of C/T treatment were included, mostly consisting of targeted treatments (83.9%) for the following sources of infection: intra‐abdominal (22.6%), urinary tract (25.8%), skin and soft tissue (19.4%), hospital‐acquired pneumonia (14%), and other (6.4%). The most frequently isolated bacteria were carbapenem‐resistant (88, 94.6%). Clinical failure rate was 30.1%, due to persistent infection at day 7 (4.3%), recurrence of the initial infection (16.1%), or 30‐day all‐cause mortality (8.6%). Adverse events most frequently reported were Clostridium difficile infection (9%) and cholestasis (8%). What is new and conclusion: C/T showed a favourable clinical profile for difficult‐to‐treat multidrug‐resistant and carbapenem‐resistant Gram‐negative infections, regardless of the source of infection. Abstract : This study provides real‐world data regarding the use of C/T to treat Gram‐negative MDR severe infections. We found that C/T was effective and well tolerated in the treatment of difficult‐to‐treat MDR and carbapenem‐resistant Gram‐negative infections, regardless of the source of infection.